NEEDS ANALYSIS: ESP SYLLABUS DESIGN FOR INDONESIAN EFL NURSING STUDENTS - Ni Kadek Ary Susandi; Ni Luh Putu Krishnawati (Universitas Negeri Padang, 2016)
Language in the field of English for Specific Purposes (ESP) is learnt to equip the learners for entry into a more specific linguistic environment, thus the most prominent feature in ESP course design is that the syllabus is based on an analysis of the students’ needs (Basturkmen 2006). The aims of this study are to explore the needs of nursing students, faculty members in the nursing department and professional nurses to design an ESP syllabus for Indonesian nursing students; also to discuss the implications for EFL teachers who teach English for Nurses. The needs analysis were conducted by distributing questionnaires to and interviewing the respondents. The answers from the respondents were analyzed based on comprehensive concept of need analysis proposed by Dudley-Evans and St. John. The findings showed that most students consider themselves as poor in vocabulary and weak in speaking, listening, writing and pronunciation. Hence, it is crucial to improve their skills to enable them communicating effectively with foreign patients and avoiding misunderstanding which may happen when interacting with foreign patients. The innovative ESP syllabus for Indonesian nurses was then developed based on these findings and the theory of material development proposed by Harding.